Analisis kelayakan usaha dan strategi pengembangan usaha peternakan lebah Trigona sp. Desa Pangkal Niur Kabupaten Bangka - Elzam; Anwar Ma’ruf; Emy Koestanty Sabdoningrum; Eduardus Bimo Aksono Herupradoto; Dadik Raharjo; M. Gandul Atik Yuliani (Fakultas Pertanian Universitas Majalengka, 2025)
This study aims to analyze the feasibility of Trigona sp. beekeeping as an alternative sustainable livelihood, identify internal and external faktors influencing business development, and formulate strategies as a basis for recommendations to beekeepers and stakeholders in ensuring sustainable growth and economic value. The research employed a survey approach using questionnaires, semi-structured interviews, and field observations, as well as a quantitative method focusing on financial analysis through the calculation of investment costs, operational costs, revenues, and feasibility indicators such as BEP, NPV, IRR, BCR, and Payback Period. Internal and external faktors were analyzed using the IFE, EFE, and IE Matrices, while development strategies were formulated through the SWOT Matrix involving 15 respondents with at least five years of beekeeping experience. The results indicate that Trigona sp. beekeeping is financially profitable and feasible to develop, as reflected by the low BEP of 44 kg/IDR 3,534,852, a positive NPV of IDR 138,067,768, an IRR of 238%, a BCR of 9.2, and a Payback Period of 0.5 (6 months). Recommended development strategies include product diversification, cultivation of feed sources, capacity building of beekeepers through training, regular product quality testing, strengthening distribution through partnerships, effective pest control, and the implementation of colony maintenance SOPs to sustain productivity and honey quality. Based on the findings, it can be concluded that Trigona sp. beekeeping is feasible and profitable to develop, supported by development strategies that emphasize product diversification, capacity enhancement, quality and distribution strengthening, as well as sustainable maintenance management to ensure economic value and long-term business sustainability.